Keputusan Menteri sosial Republik Indonesia Nomor 07/Huk/Kep/II/1984 tentang Pola dasar pembangunan bidang kesejahteraan sosial - INDONESIA._Departemen_Sosial (departemen Sosial RI, 1984)
oen, c.1/ir,c.2/stoc3=c.1-2